Age dependent plasticity in endocannabinoid modulation of pain processing through postnatal development - H-T. Kwok, Charlie; Devonshire, Ian M.; Imraish, Amer; Greenspon, Charles M.; Lockwood, Stevie; Fielden, Catherine; Cooper, Andrew; Woodhams, Stephen; Sarmad, Sarir; Ortori, Catherine A.; Barrett, David A.; Kendall, David; et al. (Lippincott, Williams & Wilkins, 2017)
Significant age and experience-dependent remodelling of spinal and supraspinal neural networks occur resulting in altered pain responses in early life. In adults endogenous opioid peptide and endocannabinoid (ECs) pain control systems exist which modify pain responses but the role they play in acute responses to pain and postnatal neurodevelopment is unknown. Here we have studied the changing role of the ECs in brainstem nuclei essential for the control of nociception from birth to adulthood in both rat and human. Using in vivo electrophysiology we show that substantial functional changes occur in the effect of microinjection of ECs receptor agonists and antagonists in the periaqueductal grey (PAG) and rostroventral medulla (RVM), both of which play central roles in the supraspinal control of pain and the maintenance of chronic pain states in adulthood. We show that in immature PAG and RVM the orphan receptor GPR55 is able to mediate profound analgesia which is absent in adults. We show that tissue levels of endocannabinoid neurotransmitters, anandamide and 2-arachidonoylglycerol within the PAG and RVM are developmentally regulated (using mass spectrometry). The expression patterns and levels of ECs enzymes and receptors were assessed using quantitative PCR and immunohistochemistry. In human brainstem we show age-related alterations in the expression of key enzymes and receptors in involved in ECs function using PCR and in situ hybridisation. These data reveal significant changes on ECs that to this point have been unknown and which shed new light into the complex neurochemical changes that permit normal, mature responses to pain.